Gedung Seni Dan Budaya Melayu Di Bengkalis Dengan Penerapan Arsitektur Rumah Tradisional Melayu Bengkalis - M, Dedy Prasetyo; Susilawaty, Mira Dharma; Firzal, Yohannes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The Malay arts and culture building in Bengkalis is a building that houses art activities and art connoisseurs in the form of performance facilities and galleries. The existence of the Malay arts and cultural building in Bengkalis is supported by an increase in the art group each year in Bengkalis and the provision of facilities and infrastructure that is not optimal. The design method of Malay art and culture building in Bengkalis uses the application of Bengkalis Malay traditional house architecture. The application of Malay traditional house architecture can be in the form of characteristics of traditional Malay home architecture in Bengkalis, namely the use of a sloping roof, stage, ornamentation, wide openings, pian tongue walls, water tanks at the front of the house, and home space programs. Dependent bee is a concept used in the management of Malay art and culture buildings, is one of the characteristics inherent in traditional Malay houses, so that the shape of the building is transformed from dependent bee formations. Keywords: Malay arts and culture building, Bengkalis, Malay traditional house architecture